VULNERABILITY OF TOURISM IN KILIMANJARO NATIONAL PARK AND THE LIVELIHOODS OF ADJACENT COMMUNITIES TO THE IMPACTS OF CLIMATE CHANGE AND VARIABILITY - Minja, Gileard (European Scientific Journal, ESJ, 2014)
The study examined the vulnerability of tourism and the livelihoods of communities adjacent to Kilimamnjaro National Park in Tanzania to the impacts of climate change. Specifically the study identified tourism resources and assessed the potential factors affecting tourism resources and activities in Kilimanjaro National Park. Further, it examined the perception of local communities on patterns of climate change and variability impacts and vulnerability in the area. Both purposeful and random sampling was used for village and household selection in the area. Both qualitative and quantitative primary and secondary data were used in this study. Primary data were mainly collected using structured household questionnaires. Participatory Rural Appraisal (PRA) methods such as questionnaires, Focus Group Discussions (FGD), key informants, timeline drivers of change and direct field observation were used to obtain data for CC&V impacts on, and vulnerability of tourism resources, activities, peoples perceptions on climate change and variability in the area. Findings revealed that climate change and variability affects tourism and resources in diverse ways. Increased drought due to CC&V fosters forest fires, melting of the glacier and decreased hydrology. People perceived CC&V as changes in both rainfall and temperature patterns over time. Decreased glacier, dry-river beds, forest fires and outbreaks of malaria were perceived as indicators of CC&V. Education, capacity building, soft loans, grants were strategies adopted to facilitate adaptation to the impacts of climate change. It is anticipated that the information obtained from this study will enable researchers, policy makers and conservation officers in National parks in Tanzania to streamline effective mitigation, coping and adaptation strategies for sustainable tourism and ecosystem protection.